Daga Ramsey - Unknown:::Creator:::::::::::: (Sag Harbor, New York, 2022)
Portrait photograph of Daga Ramsey, a Swedish American artist. Jack and Daga Ramsey were neighbors of John and Elaine's on Bluff Point Rd. in Sag Harbor, New York. Original in Safe